Rheological Modeling, Surface Morphology and Physico-chemical Properties of Anogeissus leiocarpus Gum - Okon Eddy, Nnabuk; Ameh, Paul; E. Gimba, Casmir; E. Ebenso, Eno (Asian Journal of Chemistry, 2012)
Physicochemical studies on Anogeissus leiocarpus gum (AL gum) indicated that the gum is mildly acidic, ionic, odourless, yellowish-red and is soluble in water (but insoluble in ethanol, acetone and chloroform). The gum has significant concentration of essential elements (Mg, Ca, Fe, Cu, Mn) and low concentrations of heavy metals (Pb and Cd). The protein content of the sample was also found to be low (»5 %). Scanning electron micrograph of the gum revealed that the gum is irregularly shaped and amorphous. Rheological study indicated that the viscosity of the gum increases with increasing pH and concentration but decreases with increase in temperature. The apparent activation energy of flow for Anogeissus leiocarpus gum (calculated from Arrhenius-Frenkel-Eyring plot) was 3.16 suggesting the presence of fewer inter and intra molecular interaction. Values of intrinsic viscosity obtained from Huggins and Kraemer plots were similar (8.82) while those obtained from Tanglertpaibul and Roa plots ranged from 3.50 to 11.82 dL/g. From the plot of speed of rotation versus viscosity, viscosity versus shear rate and shear stress versus shear rate, a non Newtonian behaviour (dilatant) with characteristics shear thickening property was verified for Anogeissus leiocarpus gum. Calculated ‘b’ value of 1.108 was obtained through the application of the power law equation and is associated with random coil conformation or entanglement. Analysis of the master's curve shows that random coil conformation or entanglement is proposed to occur at C[h] 4.0, i.e. at hsp = 2.19 (hrel = 3.19).